2006
DOI: 10.2353/ajpath.2006.050607
|View full text |Cite
|
Sign up to set email alerts
|

The RetC620R Mutation Affects Renal and Enteric Development in a Mouse Model of Hirschsprung's Disease

Abstract: In rare families RET tyrosine kinase receptor substitutions located in exon 10 (especially at positions 609, 618, and 620) can concomitantly cause the MEN 2A (multiple endocrine neoplasia type 2A) or FMTC (familial medullary thyroid carcinoma) cancer syndromes, and Hirschsprung's disease (HSCR). No animal model mimicking the co-existence of the MEN 2 pathology and HSCR is available, and the association of these activating mutations with a developmental defect still represents an unresolved problem. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Moreover, in ret +/C620R mice that have an enteric neuronal hypoganglionic phenotype 16 reminiscent of the histopathology observed in some CIPO patients, 27,29 Apob was markedly overexpressed. APOB is a major constituent of the plasma lipoprotein, and in mammals is synthesized in two different tissues, i.e.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, in ret +/C620R mice that have an enteric neuronal hypoganglionic phenotype 16 reminiscent of the histopathology observed in some CIPO patients, 27,29 Apob was markedly overexpressed. APOB is a major constituent of the plasma lipoprotein, and in mammals is synthesized in two different tissues, i.e.…”
Section: Discussionmentioning
confidence: 86%
“…This latter finding is reminiscent of an enteric neuronal hypoganglionic phenotype observed in heterozygous ret C620R/+ mice 16 and shares similarities with the histopathology of some CIPO patients. 14,27,28 The similarity of the rad21 suppression phenotype in zebrafish to the neuronal defects of heterozygous ret C620R/+ mice prompted us to test whether those two genes might interact genetically. We showed that RET and RAD21 interact epistatically during differentiation or maintenance of enteric neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Revealing that RET is physiologically required for the survival of colonic neurons, we set out to examine the potential involvement of Ret-dependent cell survival in ENS pathology, HSCR in particular. Although several Ret mutants have previously been reported to display aganglionosis (11,(18)(19)(20)(21)(22)(23) and so resemble HSCR to some extent, several significant differences do exist in the phenotype of those animals and that of HSCR patients. For instance, in those Ret mutant mice, the aganglionic phenotype exhibits full penetrance and is associated with kidney deficits.…”
Section: Physiological Requirement Of Ret For the Survival Of Entericmentioning
confidence: 99%
“…RET signaling also maintains the enteric nervous system, and loss of RET function in these neurons leads to Hirschsprung’s disease, a condition characterized by absence of enteric ganglia [99]. Importantly, this role of RET is reproduced in both RET knockout [100] and RET knockin mice with RET C620R mutations (mixed Hirschsprung’s/MTC phenotype)[101,102]. Finally it is important to remember that GDNF/RET signaling has a clearly established role in driving spermatogonial stem cell self-renewal in the testis, and is therefore essential to male fertility [103106].…”
Section: Molecular Pathway Dysregulations In Human C-cell Oncogenimentioning
confidence: 99%